INFLUENCES OF UPWELLING DURATION AND INTENSITY BASED ON SEA SURFACE TEMPERATURE ANOMALY TOWARD PRIMARY PRODUCTIVITY VARIABILITY IN INDONESIAN WATERS - Putri Kemili; Mutiara R. Putri (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
The existence of upwelling generally increases waters productivity. However, the influence of upwelling could be different based on location and time. The difference of upwelling duration and intensity (strength) can affect the variability of primary productivity in Indonesian waters. The estimation of primary productivity during the period of January 2000 to December 2007 was conducted using Carbon-based Production Model (CbPM). Sea Surface Temperatures (SST) Anomaly data on the same period was used as parameter to determine the upwelling conditions. The study locations were west coast of Sumatra, south waters of East Java to East Nusa Tenggara, Banda Sea, Gulf of Bone, Maluku Sea and Halmahera Sea. The results showed that in the south of East Java and Banda Sea have upwelling with longer duration (3–4 months) and higher intensity (decrease in temperature reached >2°C below average), the primary productivity was higher than other locations. Halmahera Sea showed the existence of upwelling only at certain time when El Niño occurred, while Gulf of Bone and Maluku Sea showed the occurrence of upwelling during southeast season only with 2–3 months of duration and vary intensity, which shown with the decrease in temperature ranging from 0,5–1,8oC below average. El-Niño and dipole mode in Indonesia waters generally caused longer duration and stronger intensity of upwelling producing more productivity than normal years.Keywords: Upwelling, Primary Productivity, Carbon-based Production Model